Religious Values in Novels Love at the Edge of the Prayer Rug Asma Nadia's Work: Sociology of Literature - Nasution, Tri Putri Ananda; Sembiring, Sugihana Br; Bambang Riyanto, Bambang Riyanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is qualitative research with descriptive methods. The problem studied is to find out the depictions of religious values in the novel Cinta di Ujung Sajadah by Asma Nadia. The approach used in reviewing research is with a literary sociology approach. The data collection technique was carried out by carefully reading the cibta novel at the end of the prayer mat, finding religious values, marking the text of the novel which is related to religious values, and noting the religious values contained in the novel. Based on the research results, it was concluded that there are religious values in the novel Cinta di Ujung Sajadah by Asma Nadia. First, the value of human relationship with God, namely faith, worship, patience. Second, the value of human relations with oneself, namely, sincerity, trustworthiness, honesty, maintaining personal purity, introspective, covering one's private parts, not holding grudges, and being brave. Third, the value of human relationships with other humans, namely helping each other, forgiving mistakes, being open-minded. Fourth, the value of human relations with nature, namely maintaining and preventing damage to nature and utilizing nature.